A novel negative carbon-emission, cooling, and power generation system based on combined LNG regasification and waste heat recovery: Energy, exergy, economic, environmental (4E) evaluations. (15th October 2022) - Tian, Zhen; Qi, Zhixin; Gan, Wanlong; Tian, Molin; Gao, Wenzhong
Abstract: In this paper, a novel negative carbon-emission, cooling, and power generation (NCCP) system was proposed to improve the energy efficiency of the liquid natural gas (LNG)-powered hydrogen production plant. With LNG cold energy and waste heat recovery, the NCCP system integrated organic Rankine cycle (ORC) power generation, data center cooling, and CO2 capture. The NCCP system could operate under seven scenarios and the system performance evaluations were performed via energy, exergy, economic and environmental (4 E) analysis. It was found that the NCCP system showed the best performance when all subsystems were running simultaneously. The system could produce 31.67 MW of power, 24.92 MW of cooling capacity, and 29.97 t/h of CO2 capture. The levelized energy cost and the payback period of the NCCP system were 0.071 /kWh and 7.9 years, respectively. LNG cold energy utilization efficiency, system energy efficiency, and exergy efficiency were 43.20%, 19.08%, and 29.28%, respectively. The environmental profits are validated with the negative carbon index of 29.47 t/h. Moreover, the effects of the LNG pressure, flue gas mass flow rate, and the temperature of the medium temperature shift gas on the NCCP system performances were investigated. The results show that the proposed system is a polygeneration system with the advantages of high efficiency, diversified energy output, fast return on investment, and CO2 capture. It is expected to be an energy conversion technology that could be used for reference in practical applications. Graphical abstract: Image 1 Highlights: A flexible polygeneration system is proposed for LNG cold energy recovery. The system energy efficiency and exergy efficiency are 19.08% and 46.88%. Environmental profits are validated with the negative carbon index of 29.47 t/h. The payback period of the system is 7.9 years.